Prominence of Genre A Study of the Book of Film Genre: Hollywood and Beyond - Hamed Fardar; Masoud Soflaei ShahreBabak (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this paper, the book of the genre of film, from the classical to the post-classic, has been attempted from different aspects, including the general introduction of the book and the author, the external analysis, the internal analysis and position of the book, the study of its advantages and its shortcomings. The lack of genre generation and diversity in Iranian’s films and the need for more knowledge in the field of genre studies have necessitated the publication of more books in this area. For this reason, the author’s and publisher’s efforts to convey an analytical work that examines the process of transforming the Hollywood genre from classical to post-classic and describes the genres of the film in various historical, cultural, political, and industrial fields are commendable. In this text, the author has attempted to highlight some of the main issues of the genre theory in relation to the book and a brief description of the types of published books in the genre, to show disadvantages of the form, translation, and editing of the book, to identify issues that need to be reformed.